Tinjauan Budaya Visual Adegan Pola Asuh Ayah pada Komik Digital “Bingkai Titik” Karya Gabriel Putu Dedi - Adlinia, Nabila (Qualia: Jurnal Ilmiah Edukasi Seni Rupa dan Budaya Visual, 2025)
The phenomenon of paternal parenting highlights the important role of fathers in balanced and developmentally appropriate parenting. However, in the modern era this role is often overlooked, leading to many children growing up fatherless, which impacts emotional closeness, trust and the potential for juvenile delinquency. In contrast, father involvement directly contributes to a child's physical and emotional development as well as boosting self-confidence. Gabriel Putu Dedi's Comic Frame depicts the role of fathers in parenting through silent comics. This study analyses the depiction of fatherhood using qualitative methods with Kress & van Leeuwen's visual system and metafunction analysis techniques, which include representation structure, interaction, and composition. The results explore the creator's depiction of fatherhood through visual elements in parenting scenes in episodes 7, 9, and 10.